GENETINIS DISKURSAS MEDIJŲ KULTŪROJE: GUNDYMAS PREKINIU NEMIRTINGUMU. - Rubavičius, Vytautas (Problems / Problemos, 2009)
Postmodernity is maintained as a stage of the development of capitalism. The difference between modernity and postmodernity is explained in relation to the new sphere of commodification and resourcification, namely, that of life and of all natural living processes. Postmodern media culture, or popular culture, is peopled by signs of immortality and various kinds of immortals -- cyborgs, clones, zombies, immortal human beings and others. Thus, culture accustoms a consumer to immortals and immortality which is concidered as the main goal of a human being and evolution. By nano-bio-technologies and genetic discourse this goal is made scientifically valid, thus reachable. Genetic discourse is becoming the fundamental world-view providing focal landmarks for the emerging future. Media culture supports the spreading of genetic discourse and facilitates its understanding. The temptation by immortality can be considered as a version of modernist ideology of human liberation from various natural, social and heavenly bonds. This liberation, and also secularization, is supported by a scientific genetic technological discourse which is becoming a stimulating factor of postmodern media production. The genetic explanation of the world is particularly handy for technological reflexivity: the entire world is as if encapsulated into human genes, which become the principle explaining the mystery of life, evolution and the future of humanity, thus rendering power to produce the human proper form and the future of people. All the possibilities stemming from the new genetic and biotech discoveries fell under the regulation of property relations by patenting, thus making "immortality" -- as a temptation and brand -- not only an exeptional commodity, but also a political tool and a commodifying force. As the relationships of private property have penetrated natural biogenetic diversity and, having turned it into a resource, the cognitive subject has reached the goal to secularise the Universe, which he has set for himself: only he as the owner and producer of genes lures people with the eternal shapes of the clones and their genetic information, which will be sustained in any location of the universe. the temptation by "immortality" will become even stronger when the genetic code is mastered. future of humanity is related to the mixed forms of life, trans-genic or otherwise genetically modified organisms and techno-human forms that will help to postpone, and later to conquer, death. Even thinkers with religious tendencies perceive the technological improvement of human beings as their evolution towards the techno sapiens and consider such a development as an advancement towards the Kingdom of God. The technologization of human beings is imagined in terms of their divination. yet in this case the character of contemporary science secularising God and obliterating the perception of divinity is overlooked. Two versions of immortality are analyzed more closely -- that of Z. Bauman, who links it with the development of computer technologies, and that of J. Baudrillard, who gives a warning that by cloning technologies humanity is trying to inverse the evolution and to return to the undifferentiated state of cells. The conclusion is drawn that regardless of how we understand 'immortality,' argue over its reality or unreality, all possibilities to prolong human life granted by genetics, informatics and other advances in science and technologies, which support the tempting idea of immortality, have already been penetrated by commodity relationships; therefore, "immortality" itself will be available only as a commodity.